2005
DOI: 10.1002/ijc.21143
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of metastasis of human pancreatic cancer to the liver by transportal injection of recombinant adenoviral NK4 in nude mice

Abstract: NK4, a 4-kringle fragment of hepatocyte growth factor (HGF), is an HGF antagonist that also acts as an angiogenesis inhibitor. NK4 strongly inhibits the infiltration, metastasis, and tumor growth of pancreatic cancer. The aim of our study was to evaluate the antitumor effect of adenovirus-mediated NK4 gene transfer to the liver on hepatic metastasis of pancreatic cancer in vivo. We constructed recombinant adenoviral NK4 (Ad-NK4), which encodes a secreted form of human NK4. Intrasplenic injection of Ad-NK4 indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…19 In preclinical studies, adenoviruses expressing the NK4 gene have demonstrated antitumor effects in numerous types of tumors including mesothelioma and pancreatic cancer. 65, 66 A phase I clinical study of gene therapy using the NK4 -expressing adenoviral vector in patients with mesothelioma is ongoing. 67 …”
Section: Competitive Analogs Of Hgfmentioning
confidence: 99%
“…19 In preclinical studies, adenoviruses expressing the NK4 gene have demonstrated antitumor effects in numerous types of tumors including mesothelioma and pancreatic cancer. 65, 66 A phase I clinical study of gene therapy using the NK4 -expressing adenoviral vector in patients with mesothelioma is ongoing. 67 …”
Section: Competitive Analogs Of Hgfmentioning
confidence: 99%
“…Therefore, molecular therapies for pancreatic cancer are promising new approaches to treat this often fatal disease. Investigators have used adenovirus-mediated gene transfer to treat pancreatic cancer and reported that adenovirus-mediated gene therapy inhibited progression of pancreatic cancer in vivo and in vitro (17,18). However, clinical trials revealed that it is difficult to eradicate pancreatic tumors with adenovirusmediated gene therapy alone (19,20).…”
mentioning
confidence: 99%
“…Pancreatic cancer remains one of the most malignant neoplasms because the disease is diagnosed frequently at an advanced stage, and only 3% of patients survive 5 years 1, 2, 3, 4. One of the pathological characteristics of this carcinoma is its early invasion of surrounding tissues and metastasis.…”
mentioning
confidence: 99%
“…Pancreatic cancer has various modes of spread, such as hepatic metastasis, peritoneal dissemination, retroperitoneal recurrence, lymph node metastasis and local and distant metastasis from an early stage 5. Recently, the standard drug for treatment of progressive pancreatic cancer has been gemcitabine,6 but this does not improve survival time because pancreatic cancer is highly resistant to chemotherapy 1. Therefore, more effective therapy for progressive pancreatic cancer is needed.…”
mentioning
confidence: 99%